Benefits comprehensive evaluation of demand response in SDN based on distant Grey Relational Analysis-Technique for Order Preference by Similarity to Ideal Solution - Jingmeng, Bai; Bo, Zeng; Jianhua, Zhang; Dunnan, Liu; Ming, Zeng (APPEEC 2016 : 2016 IEEE PES Asia-Pacific Power and Energy Engineering Conference : October 25-28, 2016, Xi'an, China, 2016)
In line with the inevitable requirements of social and economic development, smart distribution network (SDN) has become a major trend of the world's power grid development currently. In this paper, in-depth analysis and evaluation on benefits of user's demand response is conducted under the smart distribution network. Taking full account of the diversity of SDN participating subjects and the difference of their core interests in the market environment, we establish the relevant evaluation index system. In order to reflect the real benefits of each index more realistically and effectively, each index of different subject comprehensively covers the definite and interval data. Grey Relational Analysis-Technique for Order Preference by Similarity to Ideal Solution (GRA-TOPSIS) is used to evaluate the demand response performance of intelligent distribution network. In the evaluation process, we innovatively introduce the Expert Scoring-Interval Centric Distance (ESICD) into subjective and objective comprehensive weight method, and do objective and comprehensive empowerment for each index. At the same time, the resolution coefficient is adjusted dynamically, which will make the results more scientific and objective. Finally, under different matching mechanisms, a numerical example, evaluated synthetically on the benefit of the demand side resources with wind and light as the main body, is given to verify the feasibility of the evaluation method. Simultaneously, matching combinations with optimal demand side resources are selected, thereby, providing a strong reference to development ideas for the future development of demand-side.